2018
DOI: 10.1111/ijfs.13794
|View full text |Cite
|
Sign up to set email alerts
|

Effect of grain hardness, fractionation and cultivars on protein, pasting and dough rheological properties of different wheat flours

Abstract: Summary Coarse flour fractions (CFFs) and fine flour fractions (FFFs) obtained from flour milled from twelve different wheat cultivars varying in grain hardness index (GHI) were evaluated for particle size distribution, pasting and protein characteristics. Cultivars with greater hardness produce flour with high protein content had more proportion of large size particles. FFF had higher unextractable polymeric protein, solvent retention capacity (SRC), sedimentation value (SV) and dough stability (DS) than thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“… 248 , 250 , 269 Removal of this outer bran layer not only depletes fiber content but decreases dietary texture due to a loss of grain integrity. 249 , 268 , 269 , 270 , 271 , 272 The role of dietary fiber consumption in oral health status has been recognized predominantly from a correlative perspective. 258 , 259 , 273 , 274 In a study of fiber consumption and periodontal disease incidence among US adults, it was determined that consumption of whole grains significantly decreased periodontal disease incidence among adults aged 30 years and older.…”
Section: Diet and The Oral Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“… 248 , 250 , 269 Removal of this outer bran layer not only depletes fiber content but decreases dietary texture due to a loss of grain integrity. 249 , 268 , 269 , 270 , 271 , 272 The role of dietary fiber consumption in oral health status has been recognized predominantly from a correlative perspective. 258 , 259 , 273 , 274 In a study of fiber consumption and periodontal disease incidence among US adults, it was determined that consumption of whole grains significantly decreased periodontal disease incidence among adults aged 30 years and older.…”
Section: Diet and The Oral Microbiomementioning
confidence: 99%
“…Processing techniques seek to remove the outer, fibrous bran layer of grains to isolate the inner starch‐rich endosperm components 248,250,269 . Removal of this outer bran layer not only depletes fiber content but decreases dietary texture due to a loss of grain integrity 249,268‐272 . The role of dietary fiber consumption in oral health status has been recognized predominantly from a correlative perspective 258,259,273,274 .…”
Section: Diet and The Oral Microbiomementioning
confidence: 99%
“…A high positive correlation between the SDS-sedimentation value and gluten strength has been demonstrated (Katyal et al 2016). To determine the strength and extensibility, more elaborate tests such as the faringograph, the extensograph and alveograph have been developed that can help to predict the end useability of flour without the need of an actual baking test (AbuHammad et al 2012;Singh et al 2018). Gluten consists of polymeric high molecular weight proteins (80-130 kDa) called the high molecular weight glutenin subunits (HMW-GS), the predominantly monomeric, low molecular weight (10-70 kDa) proteins called the low molecular weight glutenin subunits (LMW-GS) and the monomeric fraction called the gliadins (kDa) (Shewry 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that small size particles increased while medium and large size particles decreased with decrease in GHI. Results reflected that wheat varieties with high GHI resulted into flour with higher proportion of large size particles and lower proportion of small size particles Singh et al (2018). (accepted) also reported the similar correlation between proportion of large size particles and GHI.…”
mentioning
confidence: 64%